Analysis of Tensile Strength of Citronella (Cymbopogon Nardus) Fiber Reinforced Composite Materials - Ardi, Julio Lukmanul; Nurdin, Hendri; Arafat, Andril; Primandani, Sri Rizki Putri (Universitas Negeri Padang, 2021)
The use of synthetic fibers in composite materials has a negative impact on the environment. One way to reduce this impact is to replace synthetic fibers with natural fibers. A natural fiber that has the potential as a mixed material in the manufacture of composite materials is citronella (Cymbopogon nardus) fiber. This study aims to determine the effect of volume fractions 40%, 50%, 60%, and 70% of citronella fiber with polyester resin matrix BQTN 157 on tensile strength. The process of making composites used the hand lay-up method. The specimen was formed according to the ASTM D3039 standard and the tensile strength of the specimen was tested by using a Universal Testing Machine (UTM). From the results of the study, the maximum tensile strength was found in the fiber volume fraction 70% of 77.35 MPa, the strain is 6.57%, and the modulus of elasticity is 1.177 GPa. This study indicates that fiber volume fraction affects the tensile strength of composite materials. Hence, the manufacture of composite materials which have good strength is influenced by many things such as raw materials, matrices, mixture composition, and methods.